Punishing places: the geography of mass imprisonment - Simes, Jessica T. (University of California Press, 2021)
A spatial view of punishment -- The urban model -- Small cities and mass incarceration -- Social services beyond the city : isolation and regional inequity -- Race and communities of pervasive incarceration -- Punishing places -- Beyond punishing places : a research and reform agenda -- Appendix : data and methodology.